Legitimacy of Zakat Distribution Across Countries: Maqasid Al-Syariah Al-Shatibi Approach - Muhammad Amin Qodri; M. Kamal Fathoni; Sulhi M. Daud; Ana Ramadhona; Afi Parnawi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines the legal and normative foundations of cross-border zakat distribution through the perspective of classical Islamic jurisprudence, contemporary positive law, and maqāṣid al-sharī‘ah. Using a normative legal research design with a doctrinal-conceptual orientation, the study integrates normative-juridical, conceptual, and comparative-juridical approaches. The analysis focuses on classical fiqh literature concerning naql al-zakāh, the maqāṣid framework of al-Shāṭibī, and zakat regulations in Indonesia and Malaysia. The findings reveal that the principle of locality (al-tawzī‘ al-maḥallī) constitutes the dominant position in classical fiqh but does not represent an absolute prohibition against cross-border zakat distribution. Rather, locality functions as a means (wasīlah) to achieve social welfare and may be set aside when greater public benefit (maṣlaḥah) and urgent humanitarian needs are present. The study further identifies a significant regulatory gap in both Indonesia and Malaysia, where existing zakat laws remain primarily domestically oriented and provide no explicit legal framework for transnational zakat distribution. Based on the operationalization of maqāṣid al-sharī‘ah, the research formulates a model of transnational zakat governance founded upon four core principles: subsidiarity, proportionality of public benefit, institutional accountability, and regulatory harmonization. This framework reconciles the tension between classical fiqh, maqāṣid-oriented reasoning, and state-based legal systems, while providing a theoretical foundation for a more adaptive and globally responsive zakat distribution mechanism capable of addressing contemporary humanitarian challenges.